Flexible, multifunctional neural probe with liquid metal enabled, ultra-large tunable stiffness for deep-brain chemical sensing and agent delivery - Wen, Ximiao (Biosens Bioelectron, 2019)
Flexible neural probes have been pursued previously to minimize the mechanical mismatch between soft neural tissues and implants and thereby improve long-term performance. However, difficulties with insertion of such probes deep into the brain severely restricts their utility. We describe a solution to this problem using gallium (Ga) in probe construction, taking advantage of the solid-to-liquid phase change of the metal at body temperature and probe shape deformation to provide temperature-dependent control of stiffness over 5 orders of magnitude. Probes in the stiff state were successfully inserted 2 cm-deep into agarose gel “brain phantoms” and into rat brains under cooled conditions where, upon Ga melting, they became ultra soft, flexible, and stretchable in all directions. The current 30 μm-thick probes incorporated multilayer, deformable microfluidic channels for chemical agent delivery, electrical interconnects through Ga wires, and high-performance electrochemical glutamate sensing. These PDMS-based microprobes of ultra-large tunable stiffness (ULTS) should serve as an attractive platform for multifunctional chronic neural implants.